Loop-miRs: active microRNAs generated from single-stranded loop regions - Winter, Julia; Link, Steffen; Witzigmann, Dominik; Hildenbrand, Catherina; Previti, A. Christopher; Diederichs, Sven (Nucleic acids research, 2013)
MicroRNAs (miRNAs) are key mediators of post-transcriptional gene regulation. The miRNA precursors are processed by the endonucleases Drosha and Dicer into a duplex, bound to an Argonaute protein and unwound into two single-stranded miRNAs. Although alternative ways to generate miRNAs have been discovered, e.g. pre-miRNA cleavage by Ago2 or cleavage products of snoRNAs or tRNAs, all known pathways converge on a double-stranded RNA duplex. Exogenous single-stranded siRNAs (ss-siRNAs) can elicit an effective RNA interference reaction; recent studies have identified chemical modifications increasing their stability and activity. Here, we provide first evidence that endogenous, unmodified, single-stranded RNA sequences are generated from single-stranded loop regions of human pre-miRNA hairpins, the so called loop-miRs. Luciferase assays and immunoprecipitation validate loop-miR activity and incorporation into RNA-induced silencing complexes. This study identifies endogenous miRNAs that are generated from single-stranded regions; hence, it provides evidence that precursor-miRNAs can give rise to three distinct endogenous miRNAs: the guide strand, the passenger strand and the loop-miR.